2014
DOI: 10.1002/humu.22604
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Cellular Phenotypes of NovelTorsinA/TOR1AMutations

Abstract: A three-nucleotide (GAG) deletion (ΔE) in TorsinA (TOR1A) has been identified as the most common cause of dominantly inherited early-onset torsion dystonia (DYT1). TOR1A encodes a chaperone-like AAA+-protein localized in the endoplasmic reticulum. Currently, only three additional, likely mutations have been reported in single dystonia patients. Here, we report two new, putative TOR1A mutations (p.A14_P15del and p.E121K) that we examined functionally in comparison with wild-type (WT) protein and two known mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…This glutamate is not the aforementioned glutamate residue in the Walker B motif, but instead is in the C-terminal α-helical domain of the AAA+ structure (Ozelius et al, 1997, Ozelius et al, 1998). A few dystonia cases have been reported to result from different TorsinA mutations (Leung et al, 2001, Zirn et al, 2008, Calakos et al, 2010, Cheng et al, 2014, Vulinovic et al, 2014). In the case of TorsinA ΔE, the disease is inherited in an autosomal dominant manner, but it is only approximately 30% penetrant (meaning not all carriers of the mutation show symptoms of the disease) (Bressman et al, 1989).…”
Section: Torsina: Disease Association and Mutant Phenotypes In Animalmentioning
confidence: 99%
See 1 more Smart Citation
“…This glutamate is not the aforementioned glutamate residue in the Walker B motif, but instead is in the C-terminal α-helical domain of the AAA+ structure (Ozelius et al, 1997, Ozelius et al, 1998). A few dystonia cases have been reported to result from different TorsinA mutations (Leung et al, 2001, Zirn et al, 2008, Calakos et al, 2010, Cheng et al, 2014, Vulinovic et al, 2014). In the case of TorsinA ΔE, the disease is inherited in an autosomal dominant manner, but it is only approximately 30% penetrant (meaning not all carriers of the mutation show symptoms of the disease) (Bressman et al, 1989).…”
Section: Torsina: Disease Association and Mutant Phenotypes In Animalmentioning
confidence: 99%
“…However, other mutations in TorsinA as well as in the cofactor LAP1 have also been associated with disease in the absence of the TorsinA ΔE302/303 mutation (Table 1). TorsinA mutations ΔA14-P15, E121K, D194V, F205I, R288Q, and ΔF323-Y328 have all been linked to specific cases of dystonia (Vulinovic et al, 2014, Cheng et al, 2014, Calakos et al, 2010, Zirn et al, 2008, Leung et al, 2001), while a LAP1 E482A mutation has been associated with severe dystonia, cerebellar atrophy, and cardiomyopathy (Dorboz et al, 2014), and a LAP1 truncation results in muscular dystrophy (Kayman-Kurekci et al, 2014). …”
Section: Rationalizing Disease-causing Mutationsmentioning
confidence: 99%
“…Both the normal function of Torsin1a and significance of the mutant protein for disease pathogenesis have been intensively studied and at least 5 cellular processes have been suggested, including roles in nuclear transport, synaptic vesicle cycling, lipid metabolism, and endoplasmic reticulum (ER) stress (Burdette et al, 2010; Chen et al, 2010; Goodchild and Dauer, 2005; Granata et al, 2011, 2008; Grillet et al, 2016; Jokhi et al, 2013; Nery et al, 2011). Although the precise cellular function(s) of Torsin1a and the pathogenic mechanism of ΔE Torsin1a remain uncertain, multiple independent laboratories have observed that the ΔE mutation has a dramatic effect on Torsin1a subcellular localization (Bragg et al, 2004; Calakos et al, 2010; Giles et al, 2008; Gonzalez-Alegre and Paulson, 2004; Goodchild and Dauer, 2005, 2004; Goodchild et al, 2005; Hewett et al, 2000, 2008; Kustedjo et al, 2000; Liang et al, 2014; Vander Heyden et al, 2009; Vulinovic et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Notably, there have been multiple cases of dystonia correlated with mutations in TorA [28-32] and several recent reports of dystonia, muscular dystrophy, and cardiomyopathy caused by mutations in LAP1 [33,34] (Table 1). The recent biochemical and mouse model advances described above have placed us in a position to rationalize these disease-causing mutations: the majority of these mutations map to or near the activator interface, suggesting that they likewise perturb the Torsin activation mechanism [35].…”
Section: Introductionmentioning
confidence: 99%